HIP ARTHROPLASTY IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - V. V. Mukhanov; A. V. Rybnikov; T. V. Popkova; M. A. Makarov (Научно-практическая ревматология)
Systemic lupus erythematosus (SLE) is a systemic autoimmune rheumatic disease of unknown etiology, characterized by the overproduction of organ-specific autoantibodies to various components of the cell nucleus and by the development of immune-mediated inflammatory damage to internal organs. A special place in the spectrum of joint injuries in patients with SLE is occupied by osteonecrosis (ON) that is considered as a severe complication of the disease. Recent advances in the diagnosis and treatment of SLE and a considerable increase in patient survival rates necessitate maintenance of the adequate quality of life for patients. In hip ON, total arthroplasty is the main method for surgical correction, which makes it possible to control pain and to improve quality of life and functional ability in patients. Despite the rather long history of applying this method, the problem of assessing the long-term results of total hip arthroplasty and the incidence of postoperative complications in patients with SLE has not been fully investigated.